2018
DOI: 10.18632/oncotarget.24845
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CAmutation, reduced AKT serine 473 phosphorylation, and increased ERα serine 167 phosphorylation are positive prognostic indicators in postmenopausal estrogen receptor-positive early breast cancer

Abstract: Although endocrine therapy is the most important treatment option in estrogen receptor (ER)-positive breast cancer, new strategies, such as molecular targeted agents together with endocrine therapy are required to improve survival. PIK3CA is the most frequent mutated gene in ER-positive early breast cancers, and PIK3CA mutation status is reported to affect activation of AKT and ERα. Moreover, recent studies demonstrate that patients had a better prognosis when tumors expressed ER, androgen receptor (AR), and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
1
7
1
Order By: Relevance
“…Its somatic mutation frequency in our MBC cohort (36%) was in between that reported by Piscuoglio et al (MBC;20%) and ER-positive FBC (n = 1431; 48%). PIK3CA mutations were associated with more aggressive tumor characteristics and reduced survival, in line with findings in ER-positive FBC subgroups (Pereira et al 2016, Ishida et al 2018. Aside from PIK3CA, the serine/threonine protein kinase AKT1 was the only other mutated gene with hotspots corresponding to FBC.…”
Section: Discussionsupporting
confidence: 77%
“…Its somatic mutation frequency in our MBC cohort (36%) was in between that reported by Piscuoglio et al (MBC;20%) and ER-positive FBC (n = 1431; 48%). PIK3CA mutations were associated with more aggressive tumor characteristics and reduced survival, in line with findings in ER-positive FBC subgroups (Pereira et al 2016, Ishida et al 2018. Aside from PIK3CA, the serine/threonine protein kinase AKT1 was the only other mutated gene with hotspots corresponding to FBC.…”
Section: Discussionsupporting
confidence: 77%
“…Mutations of the PIK3CA gene are frequently observed in luminal A (49%) and luminal B (32%) subtypes 4 , 29 . Approximately 95% of mutations exist in the helical domain (exon 9, commonly E542 and E545) and the kinase domain (exon 20, commonly H1047) 30 .We and others previously reported that PIK3CA mutations were a positive prognostic marker in ER-positive, HER2-negative early breast cancer 31 33 . In contrast, activation of the PI3K pathway is suggested to cause endocrine resistance in ER-positive advanced breast cancer, and therefore inhibitors for PI3K, AKT, and mTOR have potential therapeutic utility in patients with this tumor subtype 12 , 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the literature, no clear relationship between PIK3CA mutations and lymph node metastasis or histopathological diagnosis was observed [ 25 , 36 , 42 , 43 , 44 ]. In most of the analyzed publications, a significant relationship between the prevalence of mutations and the expression of the ER and PR receptors was observed [ 4 , 45 ]. In our cohort, the detected mutations do not depend on the expression level of those receptors.…”
Section: Discussionmentioning
confidence: 99%